1995
DOI: 10.1002/oti.6150020104
|View full text |Cite
|
Sign up to set email alerts
|

The impact on occupational therapists of the reorganisation of psychiatric care in Sweden

Abstract: The present study focuses on the on-going reorganisation of psychi atric care in a major county council in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In Sweden, occupational therapists are health care professionals who have contributed to an awareness of the need for work and occupational programs for people with long-term mental illness. Therapists realized in the late 1980s that suitable settings for the provision of occupation and work for people who were mentally ill were almost nonexistent (Gahnström-Strandqvist, Andersson, & Josephsson, 1995). However, new arenas for occupation and work have been developed; these new occupational settings are client-centered, and, to varying degrees, are managed by the participants.…”
mentioning
confidence: 99%
“…In Sweden, occupational therapists are health care professionals who have contributed to an awareness of the need for work and occupational programs for people with long-term mental illness. Therapists realized in the late 1980s that suitable settings for the provision of occupation and work for people who were mentally ill were almost nonexistent (Gahnström-Strandqvist, Andersson, & Josephsson, 1995). However, new arenas for occupation and work have been developed; these new occupational settings are client-centered, and, to varying degrees, are managed by the participants.…”
mentioning
confidence: 99%
“…Occupational therapists in psychiatric care have earlier been shown to adapt willingly to changing organizational demands [1], and they were especially motivated to accept changing policies with the focus on alternative living and occupational facilities. Still, there was no difference between the groups in the present study in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that occupational therapists in psychiatric care tend to adapt to and show positive attitudes towards organizational change [1] and that the organization shapes psychiatric occupational therapists' work [2]. Relatively recently a new reform, the Mental Health Care Reform, was adopted in Sweden [3]; it came into effect in January 1995 [4].…”
Section: Introductionmentioning
confidence: 99%